Not in Employment, Education or Training (NEET); more than a youth policy issue - Mitrou, Francis; Haynes, Michele; Perales, Francisco; Stephen, Zubrick; Baxter, Janeen (International Journal of Population Data Science, 2021)
Introduction Australians who are Not in Employment, Education or Training (NEET) and receive income support span a wide spectrum of working ages. Australian research has concentrated on NEETs aged 15--29 years, in line with international standards. This paper investigates extending the NEET concept to include all working age persons 15--64 years and the value added to welfare policy through analysis of a new linked dataset. Methods An observational study design was implemented with individuals aged 15-64 years recorded as receiving Department of Social Services (DSS) income support payments from September 2011 being linked with Australian Bureau of Statistics (ABS) Census data from August 2011 to create a linked dataset for analysis. Descriptive analyses were undertaken of NEET status by Census socio-demographic characteristics, and we modelled the adjusted likelihood of NEET status by Census demographics. Results Some 1.37 million or 45.2% of linked DSS payment recipients qualified as NEET. Of NEETs, more than twice as many were female, nearly half were aged 45--64 years, and under 1-in-5 were aged 15--29 years. Multivariate analyses showed that NEETs were more likely to be older, have low educational attainment, have a disability, and to be Indigenous. Conclusions Young NEETs aged 15--29 years represented less than 20% of linked DSS payment recipients classified as NEET, suggesting that standard NEETs reporting neglects information on around 80% of the working age NEET population in Australia. Combined with other demographic insights, these results have implications for welfare policy, and indicate a wider range of demographics should be considered under the NEET classification. This may also have implications for Organisation for Economic Co-operation and Development (OECD) reporting.